Emotional characteristics of socially isolated older adults with MCI using tablet administered NIH toolbox: I‐CONECT study. Issue 1 (11th November 2022) - Yu, Kexin; Wild, Katherine; Dowling, N. Maritza; Kaye, Jeffrey A.; Silbert, Lisa C.; Dodge, Hiroko H.
Abstract: Introduction: Examining the emotional functioning of individuals with mild cognitive impairment (MCI) could help describe their cognitive status and inform the development of interventions. This study compared the emotional characteristics of socially isolated older adults with and without MCI. Methods: We used baseline data from the Internet‐based Conversational Engagement Clinical Trial. Emotional characteristics were assessed with the National Institutes of Health Toolbox Emotion Battery (NIHTB‐EB). MCI status was determined with a consensus clinical diagnosis. Results: This study included 163 participants (mean age = 81.2 years, non‐Hispanic Black = 20.7%, MCI = 52.8%). MCI was associated with higher negative affect and lower psychological well‐being. Non‐Hispanic Black participants scored lower in sadness, higher in positive affect, and higher in meaning and purpose than non‐Hispanic White participants. Conclusion: Older adults with MCI experience more negative emotions and worse psychological well‐being than those with normal cognition. The NIHTB‐EB appears to be a sensitive tool to detect emotional characteristics associated with cognitive decline.